DRINKING WATER OF THE SURROUNDING AREAS OF KOKAND CITY AND THEIR COMPARATIVE ANALYSIS - R. A. Paygamov; G’. M. Ochilov; O. M.Valiyeva (Galaxy International Interdisciplinary Research Journal, 2023)
Of the President of the Republic of Uzbekistan No. PF-60 dated 28.01.2022 "On the Development Strategy of New Uzbekistan for the years 2022-2026" : Fundamental reform of the water resources management system and important tasks for the implementation of a separate state program on water saving [1].In this regard, effective use of water resources in our increasingly developing republic and supply of quality drinking water to the population are among the most urgent tasks.